Efeitos neurocomportamentais da taurina em modelos de exposição ao etanol e de crise convulsiva em peixe-zebra - Fontana, Barbara Dotto (2018)
Alternative translational models have been widely used in neuroscience for assessing several neurological and neuropsychiatric diseases. In this context, the emergent use of zebrafish (Danio rerio) has been relevant due to the high genetic conservation and the ability to perform high-throughput screens. Thus, in our first article, we aimed to evaluate the developing utility of zebrafish as an experimental model organism to later use evaluate the potential protector effects of taurine (TAU) in different situations. TAU is an endogenous molecule that has pleiotropic actions, such as neuromodulation, antioxidant activity, osmoregulation and membrane stabilization. The neuromodulatory action of TAU action occurs mainly through GABAA and glycine agonism. Several drugs can alter the functionality of GABAA receptors and modify the balance of inhibitory/excitatory synapses, such as ethanol (EtOH) and pentylenetetrazol (PTZ). Therefore, in our second and third works we analyzed the effects of TAU in preventing different EtOH-induced behavioral modifications, such as aggression, social interaction deficits,and changes in risk evaluation. Animals were exposed for 1 hour and divided into 8 groups: Control; TAU 42 mg/L; TAU 150 mg/L; TAU 400 mg/L; 0.25% EtOH (v/v); TAU 42/EtOH; TAU 150/EtOH and TAU 400/EtOH. Afterwards, fish were submitted to the aggression test, shoal behavior test, social preference test, and predator test. TAU exerted a biphasic effect on the aggressive behavior, where the lowest and highest concentration tested (42 and 400 mg/L) positively modulated aggression, while 150 mg/L exerted an anti-aggressive action. Additionally, temporal analysis of shoal behavior showed that EtOH alone and associated to TAU reduced social behaviors. However, in the social preference test only TAU 400/EtOH reduced conspecific preference. Regarding the aversive behavior, TAU alone and in association decreased the number of risk assessment in the predator area. Finally, we evaluated the protective role of TAU in PTZ-challenged animals and analyzed the occurence of seizures as well as changes in oxidative stress-related parameters. In this experiment, fish were pretreated with TAU (42, 150 or 400 mg / L) for 40 minutes and then exposed to PTZ for 20 minutes. Seizure scores were analyzed every 30 seconds during PTZ exposure and seizure intensity was quantified. Regarding theoxidative stress, the following parameters were analyzed: CAT, SOD, and GST activities, lipid and protein damage, as well as cellular viability and cellular death. TAU 150 mg/L attenuated PTZinduced seizures by reducing the seizure intensity and protecting against lipid and protein damage. Collectively, TAU modulates different neurochemical and behavioral responses depending on the concentration, suggesting a complex effect on different receptors and/or neural transduction pathways.